2015
DOI: 10.1158/2159-8290.cd-15-0748
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Heterogeneity and Receptor Coamplification Drive Resistance to Targeted Therapy inMET-Amplified Esophagogastric Cancer

Abstract: MET inhibition is effective in some MET-amplified esophagogastric cancer (EGC) patients, but understanding acquired and de novo resistance mechanisms will be critical to improving therapy. We identified KRAS mutation as a novel cause of acquired resistance in a patient after a two-year response to MET inhibitor. We also observed that 40–50% of MET-amplified EGC patients harbor co-amplification of HER2 and/or EGFR concurrently in the same tumor cells, which can drive de novo resistance. One patient with concurr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(144 citation statements)
references
References 28 publications
(45 reference statements)
3
126
0
1
Order By: Relevance
“…Emerging clinical reports are consistent with our hypothesis that targeted therapies may fail in patients with GEA because the biomarker being tested to guide therapy is heterogeneously present within the patients' cancer. For instance, discordance in amplification of MET and other RTKs between the PT and metastatic sites has been shown to lead to failure of MET inhibition (35). In a recent FGFR inhibitor trial that was guided by FGFR2 amplification testing of the PT, many patients with FGFR2 + PTs failed to respond.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging clinical reports are consistent with our hypothesis that targeted therapies may fail in patients with GEA because the biomarker being tested to guide therapy is heterogeneously present within the patients' cancer. For instance, discordance in amplification of MET and other RTKs between the PT and metastatic sites has been shown to lead to failure of MET inhibition (35). In a recent FGFR inhibitor trial that was guided by FGFR2 amplification testing of the PT, many patients with FGFR2 + PTs failed to respond.…”
Section: Discussionmentioning
confidence: 99%
“…The ALK inhibitor crizotinib is well known to also bind to MET tyrosine kinase domain and has shown clinical activity in MET -amplifi ed cancers ( 24,25 ). Moreover, recent phase I data showed that crizotinib may be safely combined with vemurafenib without occurrence of signifi cant dose-limiting toxicities ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 MET amplification has been identified as a relevant molecular alteration in thoracic and upper abdominal cancers. 47 Indeed, multiple studies have demonstrated durable responses to MET inhibition among patients with MET -amplified cancers, including patients with CUP. 3,47 …”
Section: Discussionmentioning
confidence: 99%